Study of Drying Kinetics and Functional Properties of Dietary Fiber Concentrates from Papaya by-Products - Nieto Calvache, Jhon Edinson (2018)
Objectives: To analyze the drying kinetics and functional properties of Dietary Fiber Concentrates (DFCs), produced from papaya by-products (pulp or peel) dehydrated by microwave or hot air convection at 40°C. Methods/Statistical analysis:The DFCs were produced by modulating three variables through a response surface design. Drying curve of each design system was fitted to the Page model. Subsequently, DFCs dehydrated by microwave or hot air convection at 40°C wereproduced. The results of these two drying methods were compared in terms of the drying kinetics (Page or Logarithmic model) and the water and oil absorption properties of the DFCs. Findings: It was found that the temperature applied for drying had a significantly negative effect on the drying time and a positive effect on the K constant of the Page model. Drying times for dehydration assisted by microwave were lower than for convection drying. In general, DFCs dehydrated by microwave presented better water and oil absorption properties. These results may be related to structural differences in the matrix, which was found to be more porous, especially in the pulp DFC dehydrated by microwaves. These studies contribute to the understanding of the effect of the drying mechanism on the drying time and functional properties of the DFCs. Application/Improvements: This study shows that papaya by-products dehydrated by microwaves have huge potential to be reprocessed and used as food ingredients as sorbent of water and/or oil.